Lepota in kerigma v tehnološki dobi - Stegu, Tadej (Bogoslovni vestnik, 2023)
The paper deals with the role of image and beauty in the kerygmatic renewal of catechesis. In today’s technological age, the digital is no longer just part of existing cultures, but is emerging as a new culture that is changing the language and the way we think. The Catechesis is challenged to reflect on the form of the faith quest of digital youth and to adapt its vocabulary to the language of the new generations. The kerygmatic renewal of catechesis underlines the beauty of Christian life and salvation and of relationships in Christian communion and connects with the theology of beauty. Christianity needs to rediscover its beauty, the beauty of life with Christ, if it is to be attractive. The kerygma, the proclamation of God’s love and mercy, helps the individual to overcome fear and absurdity as he enters a new dimension of relationship that does not end in death.
Keywords: beauty; catechesis; image; kateheza; kerigma; kerygma; lepota; odrešenost; podoba; salvation; technological age; tehnološka doba